Low leaching spinel / functionalized biochar composite disinfection material, preparation method and application

CN123002979APending Publication Date: 2026-10-30SHAANXI COAL & CHEM TECH INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129554.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]针对现有技术中存在尖晶石型铁氧体难以在宽pH值范围内兼顾高消毒效能与极低金属溶出率的问题,本发明提供一种低溶出尖晶石/功能化生物炭复合消毒材料、制备方法及应用

Benefits of technology

本发明提供一种低溶出尖晶石/功能化生物炭复合消毒材料,该材料通过功能化生物炭载体表面富含的氮、硫杂原子官能团与尖晶石活性组分中的金属阳离子之间形成MN与MS配位键,将活性组分锚定于载体表面,使活性组分在反应过程中不易脱落或迁移,从界面结合层面有效抑制了金属离子向水相的释放。同时,限定尖晶石化学通式中R的掺杂系数为0<c≤0.2,即通过Ce、La或Al元素的晶格掺杂引起尖晶石晶格的局部畸变,增加晶格中金属阳离子的迁移能垒,使得该材料在酸性或氧化性反应条件下,金属离子难以从晶格中脱离进入液相。同时,R元素(尤其是Ce)以混合价态进入晶格后,通过电荷补偿效应进一步稳定了尖晶石的结构完整性,从而使得该材料在pH值=3的苛刻酸性条件下,Zn、Fe离子溶出率仍能分别控制在极低水平,显著优于现有技术中金属溶出率。此外,MN与MS化学键合在宽pH值范围内均能保持稳定,不受水体酸碱度变化的影响;同时,R元素掺杂增强的晶格稳定性在酸性环境中表现尤为突出,有效抑制了H+对晶格中金属离子的浸出攻击,保障了该材料在pH值=3-9的宽范围内均能维持高消毒效能,克服了现有尖晶石基类芬顿材料在酸性条件下难以兼顾高消毒效能与极低金属溶出率的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002979A_ABST
    Figure CN123002979A_ABST
Patent Text Reader

Abstract

The present application relates to the field of water treatment functional materials and safe disinfection technology, and relates to a low-dissolution spinel / functionalized biochar composite disinfection material, a preparation method and application, the present application is through nitrogen and sulfur co-doped functionalized biochar carrier and the spinel active component of chemical formula M a Fe b R c O4 (0 < c < 0.2) is arranged and bonded, the double stable mechanism of chemical bonding between the surface heteroatom functional groups of the carrier and the active component and R element lattice doping effectively inhibits the dissolution of metal ions, at the same time, the bactericidal rate of the material to escherichia coli and staphylococcus aureus remains above 99.6% in a wide range of pH value=3-9, the dissolution rates of Zn and Fe ions are less than 1.6% and 0.9% respectively, the material is suitable for disinfection treatment of drinking water and reclaimed water, and solves the problems of high metal ion dissolution rate, narrow pH value application range and weak carrier-active component interface combination of the existing spinel-based fenton disinfection material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment functional materials and safe disinfection technology, specifically to a low-leaching spinel / functionalized biochar composite disinfection material, its preparation method, and its application. Background Technology

[0002] With the continuous advancement of industrialization and the increasing urbanization, water resource security has become a growing concern across society. Pollution by pathogenic microorganisms in water bodies directly impacts public health and ecological safety; therefore, developing efficient, safe, and environmentally friendly water disinfection technologies remains a crucial research direction in the water treatment field. Among numerous water treatment disinfection technologies, the heterogeneous Fenton-like technology based on hydrogen peroxide activation is considered an ideal alternative to traditional chlorine disinfection and ozone oxidation processes due to its advantages such as strong oxidizing power, lack of persistent toxic byproducts, and mild operating conditions. The core of Fenton-like technology lies in activating hydrogen peroxide with a catalyst to generate highly reactive oxygen species with strong oxidizing capabilities, thereby achieving efficient inactivation of pathogenic microorganisms in water bodies.

[0003] In the development of heterogeneous Fenton-like catalysts, spinel ferrites (general formula MFe₂O₄, where M is a divalent metal cation, at least one of Zn, Mg, and Ni) have become one of the most widely studied catalytic materials due to their advantages such as tunable crystal structure, diverse metal valence states, relatively mature preparation processes, and good chemical stability. The structure of spinel ferrites consists of a face-centered cubic close-packed framework of oxygen ions, where tetrahedral and octahedral sites can accommodate different types of metal cations. This flexible cation occupancy mode endows the material with abundant redox active sites. Material systems represented by zinc-iron spinel (ZnFe₂O₄) have exhibited good catalytic activity in Fenton-like reactions, effectively promoting the decomposition of hydrogen peroxide and generating active species such as hydroxyl radicals, thereby achieving the oxidative removal of target pollutants or pathogenic microorganisms.

[0004] Although spinel ferrites have shown promising applications in Fenton-like catalysis, these materials generally suffer from problems such as easy dissolution of metal ions and poor long-term stability in practical water treatment applications. In acidic or neutral water environments, especially under oxidizing conditions in the presence of hydrogen peroxide, the metal cations in the spinel ferrite lattice (such as Zn)... 2+ Fe 3+ (e.g., zinc ions) can easily detach from the crystal structure and enter the aqueous phase, leading to damage to the structural integrity of the material and a gradual decline in catalytic activity. Existing studies have shown that, under conventional reaction conditions, the dissolution rates of zinc ions and iron ions in ZnFe2O4 materials prepared by traditional methods often exceed 5% and 4%, respectively. This not only severely shortens the material's lifespan but also raises concerns about the risk of secondary pollution from heavy metals.

[0005] To address the issues of short lifespan and poor catalytic activity in materials caused by metal ion leaching, existing technologies often employ elemental doping to enhance the stability of the spinel lattice, or surface coating or carrier loading to physically block the contact between the active component and the aqueous phase. For example, spinel active components are loaded onto porous carbon materials, utilizing the confinement effect and surface forces of the carrier to suppress the release of metal ions. Biochar, as a widely available and inexpensive carbon-based support material, has received increasing attention in the field of catalyst loading in recent years. However, most existing carrier loading strategies rely on non-chemical bonding forces such as physical adsorption or electrostatic interactions, resulting in limited interfacial bonding strength between the active component and the carrier. Under long-term operation or harsh water quality conditions, there is still a risk of active component detachment and metal leaching. Furthermore, some modification methods can only achieve physical barrier on the material surface and cannot suppress the lattice leaching of metal ions at the intrinsic level of the spinel crystal structure, thus having limited effect on improving the overall stability of the material. The leaching problem is particularly prominent under acidic pH conditions. Most existing spinel-based Fenton catalysts can maintain a certain level of catalytic activity in neutral or alkaline environments, but under acidic conditions (such as pH 3-5), their catalytic efficiency decreases significantly due to increased metal dissolution and deactivation of active sites, thus limiting the applicable pH range of the materials. Furthermore, the large fluctuations in pH values ​​of natural water bodies and some industrial wastewaters greatly restrict the application scenarios of these materials in practical water treatment.

[0006] Therefore, developing a spinel-based composite disinfection material that can inhibit metal leaching from the source of material structure design and has both high Fenton-like catalytic activity and wide pH adaptability is of great scientific significance and engineering value for promoting the practical application of heterogeneous Fenton-like technology in the field of water disinfection. Summary of the Invention

[0007] To address the problem in existing technologies that spinel-type ferrites cannot simultaneously achieve high disinfection efficiency and extremely low metal leaching rate over a wide pH range, this invention provides a low-leaching spinel / functionalized biochar composite disinfection material, its preparation method, and its application.

[0008] To achieve the above objectives, the present invention employs the following technical solution: This invention provides a low-dissolution spinel / functionalized biochar composite disinfection material, comprising a functionalized biochar carrier, wherein the functionalized biochar carrier is rich in nitrogen and sulfur heteroatom functional groups, and spinel active components are coordinated and bonded to it through MN and MS. The chemical formula of the spinel active component is: M a Fe b R cO4, where M is one or more of Zn, Mg, and Ni; R is one or more of Ce, La, and Al; a, b, and c are molar coefficients that satisfy charge balance and lattice structure, where 0 <c≤0.2。

[0009] Optionally, the functionalized biochar carrier is prepared by pyrolysis of agricultural waste modified with both nitrogen and sulfur sources.

[0010] Optionally, the functionalized biochar carrier is prepared by pyrolysis of a compound of urea and thiourea.

[0011] Optionally, the mass ratio of urea to thiourea is (0.8-1.2):1.

[0012] Optionally, in the chemical formula of the spinel-type ferrite, M is Zn, R is Ce, and the chemical formula is ZnFe. b Ce c O4, where b = 2 - c, 0 < c ≤ 0.2.

[0013] This invention also provides a method for preparing the low-leaching spinel / functionalized biochar composite disinfectant material as described above, comprising: The biomass raw material is impregnated in an aqueous solution containing nitrogen and / or sulfur compounds and then dried to obtain a functionalized precursor. A metal salt solution containing M, Fe, and R was mixed with a functionalized precursor, the pH value was adjusted, and co-precipitation, hydrothermal reaction, and calcination under an inert atmosphere were carried out sequentially to obtain a low-dissolution spinel / functionalized biochar composite disinfection material.

[0014] Optionally, the biomass raw material is wheat straw powder or rice husk powder; the mass concentration of the aqueous solution containing nitrogen and / or sulfur compounds is 5%-15%; the mass ratio of nitrogen source to sulfur source in the aqueous solution containing nitrogen and / or sulfur compounds is (0.8-1.2):1; the soaking time is 3-5 hours; the drying temperature is 70-90℃ and the drying time is 8-16 hours.

[0015] Optionally, in the metal salt solution containing M, Fe, and R, the mass concentration of the metal salts M, Fe, and R is 8%-15%, and the molar ratio of M, Fe, and R in the metal salt solution satisfies the general chemical formula for spinel-type ferrites M a Fe b R cThe molar ratio of the corresponding elements in O4, the ratio of the metal salt solution containing M, Fe, and R to the functionalized precursor is (15-25) mL:1g; the pH value is adjusted by titration with ammonia water, and the pH value adjustment range is 9-11; the hydrothermal reaction temperature is 160-200℃, and the time is 10-14h; the calcination temperature is 450-600℃, and the time is 3-5h; the inert atmosphere is nitrogen atmosphere; before calcination, the hydrothermal reaction product is washed to neutral and dried at 70-90℃ for 8-16h.

[0016] Application of the above-mentioned low-leaching spinel / functionalized biochar composite disinfection material in water treatment disinfection.

[0017] Optionally, the application of the low-leaching spinel / functionalized biochar composite disinfection material in water treatment disinfection includes: Low-leaching spinel / functionalized biochar composite disinfectant material and H2O2 are added to the water to be treated, and the reaction is stirred to inactivate pathogenic microorganisms. The dosage of low-leaching spinel / functionalized biochar composite disinfectant material is 0.05-0.2 g / L, the concentration of H2O2 is 2-8 mM, the reaction time is 20-40 min, and the pH value of the water to be treated is 3-9.

[0018] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a low-leaching spinel / functionalized biochar composite disinfectant material. This material utilizes the nitrogen and sulfur heteroatom functional groups abundant on the surface of the functionalized biochar carrier to form M... N and M S-coordinate bonds anchor the active component to the carrier surface, making it difficult for the active component to detach or migrate during the reaction, effectively suppressing the release of metal ions into the aqueous phase at the interfacial bonding level. Simultaneously, by limiting the doping coefficient of R in the spinel's chemical formula to 0 < c ≤ 0.2, the lattice doping of Ce, La, or Al elements causes local distortion of the spinel lattice, increasing the migration energy barrier of metal cations in the lattice. This makes it difficult for metal ions to detach from the lattice and enter the liquid phase under acidic or oxidizing reaction conditions. Furthermore, the presence of R elements (especially Ce) in the lattice in a mixed valence state further stabilizes the structural integrity of the spinel through charge compensation effects. This allows the dissolution rates of Zn and Fe ions to be controlled at extremely low levels even under harsh acidic conditions (pH=3), significantly better than the metal dissolution rates in existing technologies. In addition, M... N and M S chemical bonds remain stable over a wide pH range, unaffected by changes in water pH; meanwhile, the enhanced lattice stability from R doping is particularly pronounced in acidic environments, effectively suppressing H... +The leaching attack on metal ions in the crystal lattice ensures that the material can maintain high disinfection efficiency over a wide pH range of 3-9, overcoming the problem that existing spinel-based Fenton materials cannot achieve both high disinfection efficiency and extremely low metal leaching rate under acidic conditions.

[0019] This invention also provides a method for preparing the low-dissolution spinel / functionalized biochar composite disinfection material as described above. This method involves pre-introducing nitrogen and sulfur heteroatom functional groups onto the surface of a biomass carrier to enable chemical coordination. Then, after mixing a metal salt solution with the functionalized precursor, the metal cations first undergo complexation coordination with the heteroatom functional groups on the carrier surface, i.e., precursor complexation assembly. Subsequently, co-precipitation allows the spinel precursor to nucleate and grow in situ on the carrier surface, ensuring that the active component establishes a chemical bond with the carrier from the initial formation stage. This fundamentally strengthens the interfacial bonding strength between the carrier and the active component. Combined with a low-temperature hydrothermal precrystallization agent and high-temperature pyrolysis lattice reconstruction, the final material contains M... N and M The S-coordinate bonds are fully formed, and the spinel lattice is fully developed while the R-element is effectively doped and solidified. This facilitates the formation of a structurally complete spinel lattice with controllable defects, thereby enhancing the lattice's ability to bind metal ions. This overcomes the weakness of interfacial bonding caused by physical mixing or simple impregnation in existing technologies, and improves the chemical stability and conductivity of the support, which is beneficial for electron transfer processes in Fenton-like reactions. This method is simple, operates under mild conditions, does not require complex preparation equipment, and exhibits good process stability, making it suitable for industrial-scale production.

[0020] The application of the aforementioned low-leaching spinel / functionalized biochar composite disinfection material in water treatment disinfection is highly effective due to its extremely low metal leaching rate and wide pH adaptability. This allows it to work effectively in acidic, neutral, and even weakly alkaline water bodies without the need for pre-adjustment of the water's pH, significantly simplifying the actual water treatment process and reducing treatment costs. Simultaneously, the extremely low metal leaching rate ensures that the material will not rapidly deactivate due to the loss of active components during long-term use, extending its service life. Furthermore, it effectively prevents the secondary release of heavy metal ions into the treated effluent, ensuring the safety of the effluent and achieving highly efficient inactivation of pathogenic microorganisms in the water. It offers excellent ease of operation and cost-effectiveness, making it suitable for various practical scenarios such as advanced drinking water treatment, reclaimed water disinfection, and emergency response to sudden water pollution. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the preparation method of a low-dissolution spinel / functionalized biochar composite disinfection material according to the present invention.

[0022] Figure 2The graphs show the comparison of metal ion dissolution rate and sterilization rate of the materials prepared in the embodiments and comparative examples of the present invention under an acidic reaction system with a pH of 3. In the graphs, a is the comparison of metal ion dissolution rate and b is the comparison of sterilization rate.

[0023] Figure 3 The graph shows the comparison of the metal ion dissolution rate and sterilization rate of the materials prepared in Example 1 (Cat-1), Example 3 (Cat-3), and Example 7 (Cat-7) with respect to the pH value of the reaction system. In the graph, a is the metal ion dissolution rate and sterilization rate of the material prepared in Example 1, b is the metal ion dissolution rate and sterilization rate of the material prepared in Example 3, and c is the metal ion dissolution rate and sterilization rate of the material prepared in Example 7.

[0024] Figure 4 For the reaction time of Example 1 (Cat 1) Effect of material sterilization rate on metal ion leaching rate.

[0025] Figure 5 For the amount of material added in Example 1 (Cat) 1) Effect of material sterilization rate on metal ion leaching rate.

[0026] Figure 6 Example 1 (Cat) 1) Example 3 (Cat) 3) Comparative Example 1 (Ref) 1) Comparative Example 2 (Ref) 2) and ZnFe2O4 standard card (JCPDS No. 22) X-ray diffraction (XRD) pattern of 1012.

[0027] Figure 7 Example 1 (Cat) 1) Scanning electron microscope (SEM) image of the nitrogen-sulfur co-doped functionalized biochar support used.

[0028] Figure 8 Example 1 (Cat) 1) Scanning electron microscope (SEM) images of the material.

[0029] Figure 9 Example 1 (Cat) 1) Compared with Comparative Example 1 (Ref) 1) High-resolution X-ray photoelectron spectroscopy (XPS) spectra of the N1s, S2p and Ce3d orbitals of the material, where a is the high-resolution X-ray photoelectron spectroscopy spectrum of the N1s orbital, b is the high-resolution X-ray photoelectron spectroscopy spectrum of the S2 orbital, and c is the high-resolution X-ray photoelectron spectroscopy spectrum of the Ce3d orbital. Detailed Implementation

[0030] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0032] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0033] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0034] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0035] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0036] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0037] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.

[0038] This invention provides a low-dissolution spinel / functionalized biochar composite disinfection material, including a functionalized biochar carrier. The functionalized biochar carrier is obtained by modifying and pyrolyzing agricultural waste through a nitrogen source and a sulfur source. The functionalized biochar carrier is rich in nitrogen and sulfur heteroatom functional groups and has spinel active components coordinated and bonded to it through MN and MS. The chemical formula of the spinel active component is: M a Fe b R c O4, where M is one or more of Zn, Mg, and Ni; R is one or more of Ce, La, and Al; a, b, and c are molar coefficients that satisfy charge balance and lattice structure, where 0 <c≤0.2。

[0039] Preferably, the functionalized biochar carrier is prepared by pyrolysis of a compound of urea and thiourea. The mass ratio of urea to thiourea is (0.8-1.2):1. In the spinel-type ferrite, M is Zn, R is Ce, and the chemical formula is ZnFe. b Ce c O4, where b = 2 - c, 0 < c ≤ 0.2.

[0040] See Figure 1 The present invention also provides a method for preparing the above-mentioned low-leaching spinel / functionalized biochar composite disinfectant material, comprising: S1: The biomass raw material is impregnated in an aqueous solution containing nitrogen and / or sulfur compounds, and then dried to obtain the functionalized precursor, specifically: Biomass raw materials, such as wheat straw powder or rice husk powder, are soaked in an aqueous solution containing nitrogen and / or sulfur compounds at a mass concentration of 5%-15% for 3-5 hours and dried at 70-90℃ for 8-16 hours to obtain a functionalized precursor; wherein the mass ratio of nitrogen source to sulfur source in the aqueous solution containing nitrogen and / or sulfur compounds is (0.8-1.2):1.

[0041] S2: A metal salt solution containing M, Fe, and R is mixed with a functionalized precursor, the pH value is adjusted, and co-precipitation, hydrothermal reaction, and calcination under an inert atmosphere are performed sequentially to obtain a low-leaching spinel / functionalized biochar composite disinfection material, specifically: Metal salts of M, Fe, and R are dissolved in water to form a metal salt solution containing M, Fe, and R with a mass concentration of 8%-15%. Among them, M salt is a water-soluble divalent metal salt, preferably a nitrate, but soluble salts such as sulfates, chlorides, or acetates can also be used. Preferred salts are zinc salts (zinc nitrate (Zn(NO3)2·6H2O), zinc sulfate (ZnSO4·7H2O) or zinc chloride (ZnCl2)), magnesium salts (magnesium nitrate (Mg(NO3)2·6H2O), magnesium sulfate (MgSO4·7H2O), magnesium chloride (MgCl2·6H2O)) and nickel salts (nickel nitrate (Ni(NO3)2·6H2O), nickel sulfate (NiSO4·6H2O), nickel chloride (NiCl2·6H2O))). The Fe salt is preferably ferric nitrate (Fe(NO3)2·9H2O), but ferric sulfate (Fe2(SO4)3) or ferric chloride (FeCl3·6H2O) can also be used; the R salt is preferably cerium salt (cerium nitrate (Ce(NO3)3·6H2O), cerium sulfate (Ce(SO4)2), cerium chloride (CeCl3·7H2O)), lanthanum salt (lanthanum nitrate (La(NO3)3·6H2O), lanthanum chloride (LaCl3·7H2O)) or aluminum salt (aluminum nitrate (Al(NO3)3·9H2O), aluminum sulfate (Al2(SO4)3), aluminum chloride (AlCl3·6H2O))). The molar ratio of M, Fe, and R in the metal salt solution satisfies the general chemical formula M for spinel-type ferrites. a Fe b R c The molar ratio of corresponding elements in O4; A metal salt solution containing M, Fe, and R was mixed with a functionalized precursor at a ratio of (15-25) mL:1 g. The pH value was adjusted by titration with ammonia water to a range of 9-11. After co-precipitation was induced by stirring at room temperature, the mixture was transferred to a hydrothermal reactor and subjected to hydrothermal reaction at 160-200℃ for 10-14 h. The hydrothermal reaction product was washed until neutral and dried at 70-90℃ for 8-16 h. Under an inert atmosphere, the temperature was increased to 450-600℃ at a rate of 3-8℃ / min and calcined for 3-5 h to obtain a low-dissolution spinel / functionalized biochar composite disinfection material.

[0042] The application of the aforementioned low-leaching spinel / functionalized biochar composite disinfection material in water treatment disinfection is as follows: Low-leaching spinel / functionalized biochar composite disinfectant material and H2O2 are added to the water to be treated, and the reaction is stirred to inactivate pathogenic microorganisms. The dosage of low-leaching spinel / functionalized biochar composite disinfectant material is 0.05-0.2 g / L, the concentration of H2O2 is 2-8 mM, the reaction time is 20-40 min, and the pH value of the water to be treated is 3-9.

[0043] Example 1 A method for preparing a nitrogen-sulfur co-doped biochar-supported cerium-doped spinel composite disinfectant material includes the following steps: Carrier surface functionalization: 5.0g of wheat straw powder (100 mesh) was immersed in 100mL of modifier aqueous solution for 4h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%; and dried at 80℃ for 12h.

[0044] Precursor complexation assembly: 2.97g Zn(NO3)2·6H2O, 7.68g Fe(NO3)2·9H2O, and 0.43g Ce(NO3)3·6H2O were dissolved in 100mL of deionized water. The above precursors were added and stirred for 30min to allow the metal cations to complex with the heteroatom functional groups on the support surface.

[0045] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 hours to induce coprecipitation; then it was transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 12 hours, followed by natural cooling.

[0046] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12 h; then heated to 550℃ at a rate of 5℃ / min under N2 atmosphere and calcined for 4 h to complete the graphitization of the carbon matrix and the Ce-reconstruction of the spinel lattice. 3+ After doping and curing, and cooling, the mixture was ground through a 200-mesh sieve to obtain the target composite material Cat-1 (ZnFe). 1.9 Ce 0.1 O4 / NSC).

[0047] Example 2 The preparation method is the same as in Example 1, except that the amount of Ce(NO3)3·6H2O is adjusted to 0.22g and the amount of Fe(NO3)2·9H2O is adjusted to 7.88g, while keeping the total molar amount of metal constant, to obtain the target composite material Cat-2.

[0048] Example 3 The preparation method is the same as in Example 1, except that Ce(NO3)3·6H2O is not added, and the amount of Fe(NO3)2·9H2O is adjusted to 8.08g, which is denoted as Cat-3.

[0049] Example 4 The preparation method is the same as in Example 1, except that the modifier is replaced with a 10% (w / w) aqueous solution of single urea, and no thiourea is added. This is designated as Cat-4.

[0050] Example 5 The preparation method is the same as in Example 1, except that the modifier is replaced with a 10% (w / w) aqueous solution of thiourea and no urea is added. This is designated as Cat-5.

[0051] Example 6 The preparation method is the same as in Example 1, except that the wheat straw powder is replaced with rice husk powder, which is denoted as Cat-6.

[0052] Example 7 The preparation method is the same as in Example 1, except that the modifier is a mixture of urea and thiourea at a mass ratio of 0.8:1, with the total mass fraction still being 10%, denoted as Cat-7.

[0053] Example 8 The preparation method is the same as in Example 1, except that the modifier is changed to a mixture of urea and thiourea at a mass ratio of 1.2:1, with the total mass fraction still being 10%, denoted as Cat-8.

[0054] Example 9 The preparation method is the same as in Example 1, except that the hydrothermal reaction temperature is adjusted to 160°C and the calcination temperature is adjusted to 450°C, and it is denoted as Cat-9.

[0055] Example 10 The preparation method is the same as in Example 1, except that the hydrothermal reaction temperature is adjusted to 200℃ and the calcination temperature is adjusted to 600℃, which is denoted as Cat-10.

[0056] To verify the influence of material structure and composition on performance, the following comparative examples were set up.

[0057] Comparative Example 1 The preparation method is the same as in Example 1, except that the carrier functionalization process is replaced by using 5.0g of wheat straw powder (100 mesh) directly as the carrier without urea / thiourea solution impregnation and modification treatment, which is referred to as Ref-1.

[0058] Comparative Example 2 Without adding wheat straw powder or modifiers, using only the metal salt formulation (containing Ce) from Example 1, pure spinel material was obtained through a co-precipitation-hydrothermal-calcination process, denoted as Ref-2.

[0059] To investigate the influence of material composition on its performance, the materials prepared in Examples 1-10 and Comparative Examples 1-2 were tested for metal ion dissolution rate and bacterial inactivation efficiency. A pH of 3.0 was selected as the baseline environment to assess the material's tolerance under acidic conditions. Specific conditions were: material dosage 0.1 g / L, H₂O₂ concentration 5.0 mM, reaction time 30 min, and the test bacteria were *Escherichia coli* and *Staphylococcus aureus*. Results are as follows: Figure 2 As shown.

[0060] based on Figure 2Based on the data, a control system of Cat-1, Cat-3, and Ref-1 was constructed. Under the condition of no Ce doping, comparing Cat-3 (nitrogen-sulfur co-doped) and Ref-1 (without nitrogen-sulfur modification), it was found that the introduction of nitrogen-sulfur co-doped biochar support reduced the Zn ion dissolution rate from 7.5% to 2.8%, while significantly improving the microbial inactivation rate. Combined with... Figure 9 XPS characterization results showed that the heteroatom functional groups on the surface of biochar coordinated with metal ions to construct a stable composite structure. Further comparative results showed that, compared with Ref-2 (without a carrier, only the active component), under the same testing conditions, its Zn and Fe dissolution rates were as high as 8.3% and 6.5%, respectively, and its inactivation rates against both bacteria were significantly lower than those of Cat-3. This indicates that without a carrier, the active component is difficult to stabilize effectively, and the requirements of low dissolution and high sterilization cannot be met simultaneously.

[0061] While keeping the carrier modification conditions unchanged, a comparison between Cat-1 (containing Ce) and Cat-3 (without Ce) shows that the introduction of Ce further reduced the dissolution rates of Zn and Fe from 2.8% and 1.8% to 1.6% and 0.9%, respectively, and increased the bactericidal rates against Escherichia coli and Staphylococcus aureus to 99.6% and 99.5%, respectively. These results indicate that the introduction of Ce improves the stability of the spinel lattice and inhibits the dissolution of metal ions.

[0062] Cat-1 combines carrier modification and Ce doping, exhibiting optimal overall performance. Data from other embodiments further corroborate the versatility of this invention: Cat 4 (single nitrogen doping) and Cat While single sulfur doping (5) can reduce metal leaching to some extent, its inactivation rate against both bacteria is significantly lower than that of the nitrogen-sulfur co-doped system, failing to simultaneously meet the performance requirements of low leaching and high sterilization. Cat-6 (rice husk-based) performs similarly to Cat-1. The leaching rates of Cat-7 (nitrogen-sulfur ratio 0.8:1) and Cat-8 (nitrogen-sulfur ratio 1.2:1) fluctuate but remain at a low level. Cat-9 (160℃ / 450℃) and Cat-10 (200℃ / 600℃) maintain low leaching and high sterilization over a wide temperature range. The above data indicate that within the specified parameter range, the material properties exhibit a continuous and stable trend with variable adjustments, without any abrupt changes.

[0063] Further process validation results showed that materials prepared under the conditions of hydrothermal reaction times of 10h and 14h, calcination reaction times of 3h and 5h, and drying times of 8h and 16h, exhibited Zn and Fe dissolution rates below 1.3% and 1.0%, respectively, and inactivation rates against Escherichia coli and Staphylococcus aureus remained above 99.3% under the aforementioned test conditions. These data indicate that materials prepared within this process window maintained high performance levels and possessed excellent process stability.

[0064] Based on the above data, it can be seen that within the parameter range, the material properties show a continuous and stable trend of change with the adjustment of variables, without any sudden changes.

[0065] To further examine the adaptability of the material structure to different application scenarios, the optimal design Cat-1 was selected for the following system tests.

[0066] Performance under different pH conditions: To further investigate the stability of the material structure under different application scenarios, Cat-1 (optimal design), Cat-7 (boundary design), and Cat-3 (Ce-free) were selected for comparative testing. Under the conditions of 5.0 mM H₂O and a reaction time of 30 min, the effect of pH on the sterilization rate and metal leaching rate was investigated. The results are as follows: Figure 3 As shown. By Figure 3 It can be seen that Cat-1 (nitrogen-sulfur co-doped + Ce) exhibits the best overall performance within the pH range of 3–9. At pH 3.0, its kill rate against both bacteria is approximately 99.5%, with Zn and Fe dissolution rates of 1.6% and 0.9%, respectively. Under neutral conditions at pH 7.0, the kill rate remains at 99.9%, with Zn and Fe dissolution rates of 0.8% and 0.5%, respectively. Cat-7 (nitrogen-sulfur ratio 0.8:1 + Ce), designed as the boundary of the nitrogen-sulfur ratio, shows a kill rate against both bacteria of approximately 99.0% under acidic conditions at pH 3.0, with Zn and Fe dissolution rates of 1.8% and 1.2%, respectively. At pH 7.0, the kill rate increases to 99.7%, while the dissolution rate decreases to 1.0% for Zn and 0.7% for Fe. In contrast, Cat-3 (nitrogen-sulfur co-doped, without Ce) exhibited a Staphylococcus aureus sterilization rate of only 88.2% at pH 3.0, with Zn and Fe dissolution rates increasing to 2.8% and 1.8%, respectively. At pH 7.0, the sterilization rate recovered to 98.0%, while the dissolution rates decreased to 2.0% for Zn and 1.3% for Fe. These data indicate that Ce doping effectively suppressed excessive dissolution of metal ions under acidic conditions, maintaining the stability of the material structure.

[0067] The effect of reaction time: Given that pH 7.0 is close to the pH range of most natural water bodies and drinking water, this condition was chosen for the reaction time investigation. Under H₂O₂ 5.0 mM conditions, the performance changes of Cat⁻¹ within 5–60 min were tested, and the results are as follows: Figure 4 As shown. By Figure 4 It can be seen that the dissolution rates of Zn and Fe showed a slow upward trend with the extension of reaction time. At 60 min, the dissolution rate of Zn was 0.9% and that of Fe was 0.6%, both remaining at low levels. Regarding bactericidal performance, the kill rate against both bacteria was approximately 97.0% at 10 min; the kill rate increased to 99.9% at 30 min; and the kill rate remained stable within the range of 20-60 min, without showing a downward trend. The data indicate that within the range of 5-60 min, the kill rate of Cat-1 showed a continuous upward trend with the extension of reaction time; although the metal dissolution rate increased somewhat, there was no abrupt increase.

[0068] The impact of dosage: The performance of Cat-1 at different dosages was investigated under the conditions of pH=7.0, H2O2 5.0mM, and reaction time of 30 min. The results are as follows: Figure 5 As shown.

[0069] Depend on Figure 5 It can be seen that when the dosage is 0.05 g / L, the inactivation rates against Escherichia coli and Staphylococcus aureus are 85.2% and 86.5%, respectively, and the leaching rates of Zn and Fe are 0.4% and 0.2%, respectively. When the dosage is increased to 0.1 g / L, the sterilization rates increase to 99.9% and 99.9%, respectively, and the leaching rates of Zn and Fe are 0.8% and 0.5%, respectively. When the dosage is further increased to 0.2 g / L, the sterilization rate remains at a high level, and the leaching rates of Zn and Fe are 1.2% and 0.8%, respectively. The data show that within the range of 0.05-0.2 g / L, the sterilization rate increases with the increase of the dosage, and the metal leaching rate also increases accordingly.

[0070] This invention includes a series of composite materials obtained by adjusting the nitrogen-sulfur ratio, Ce content, biomass carrier type, and reaction conditions. Some embodiments illustrate the role of key components (such as Ce and nitrogen-sulfur co-doping), while others verify performance under different process conditions (such as pH, reaction time, and material dosage). Results from the representative embodiments show that, within the corresponding parameter ranges, the bactericidal rate and metal ion dissolution rate of the materials exhibit continuous and stable trends, without abrupt changes or performance degradation. These data patterns indicate that, within the parameter ranges described in the claims, the materials are expected to maintain a combination of low dissolution and high bactericidal efficiency.

[0071] To further explore the structural origin of the low dissolution and high bactericidal properties exhibited by Cat-1, a systematic physicochemical characterization of the material was performed. XRD comparative analysis was conducted using standard cards for Cat-1, Cat-3, Ref-1, Ref-2, and ZnFe2O4 (JCPDS No. 22-1012). Figure 6 It can be seen that the characteristic diffraction peak positions of Cat-1, Cat-3, Ref-1, and Ref-2 are consistent with those of the standard card, with spinel phase characteristic peaks appearing at 2θ = 30.1°, 35.5°, 43.1°, 53.4°, 56.9°, and 62.5°, and no obvious impurity phase peaks were observed. Among them, Ref-2 has the highest diffraction peak intensity and the sharpest peak shape; Cat-1's peak shape and intensity are similar; Ref-1's characteristic peaks are significantly broadened and have weaker intensity. The data indicate that spinel structures were formed in all systems, and the active components loaded on the nitrogen-sulfur co-doped supports have high crystallinity.

[0072] The product (functionalized carrier) from step (1) of the Cat-1 preparation process and the finished Cat-1 were characterized by SEM. Figure 7 As can be seen, the surface of the functionalized biochar carrier exhibits a sheet-like structure. (From...) Figure 8 It is evident that the spinel active component is loaded in particulate form on the surface and pores of the biochar carrier and is evenly distributed.

[0073] XPS characterization was performed on Cat-1 and Ref-1. Figure 9 As can be seen, the N1s and S2p spectra of Cat-1 exhibit characteristic peaks at binding energies of ~399.0 eV and ~164.0 eV, respectively; no obvious peak signals were observed in Ref-1 within the same binding energy range. Meanwhile, the Ce 3d spectrum of Cat-1 shows Ce³⁺. + / Ce 4+ Mixed valence state characteristics. Data indicate that there is an interaction between the spinel active component and the nitrogen-sulfur co-doped biochar support, and that Ce has entered the spinel lattice.

[0074] Based on the above characterization results, the structural characteristics of Cat-1 are reflected in the following two aspects: Firstly, the binding state between the active component and the support. XPS data showed MN and MS bonding signals in Cat-1, while no such signals were detected in Ref-1. This indicates that in Cat-1, a specific chemical bond is formed between the spinel active component and the nitrogen-sulfur co-doped biochar support, rather than a simple physical stacking.

[0075] Secondly, lattice structure characteristics. XPS data also show that Ce in Cat-1 exhibits a mixed valence state (Ce... 3+ / Ce 4+Based on XRD data, it is inferred that the entry of Ce into the lattice caused local structural distortion, which helped maintain the integrity of the lattice.

[0076] The above data indicate that the composite structure formed by the nitrogen-sulfur co-doped biochar carrier and the Ce-doped spinel active component jointly determines the performance of Cat-1 in terms of low metal leaching and high bactericidal properties.

[0077] Example 11 A method for preparing a low-dissolution magnesium-based lanthanum-doped spinel / functionalized biochar composite disinfection material includes the following steps: Carrier surface functionalization: 5.0 g of wheat straw powder (100 mesh) was immersed in 100 mL of modifier aqueous solution for 4 h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%. The mixture was dried at 80 °C for 12 h.

[0078] Precursor complexation assembly: Dissolve 2.56 g Mg(NO3)2·6H2O, 7.68 g Fe(NO3)2·9H2O, and 0.43 g La(NO3)3·6H2O in 100 mL of deionized water, add the above precursor, and stir for 30 min to allow the metal cations to complex with the heteroatom functional groups on the support surface.

[0079] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 hours to induce coprecipitation; then the mixture was transferred to a hydrothermal reactor and hydrothermally reacted at 180°C for 12 hours, followed by natural cooling.

[0080] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12h; then heated to 550℃ at a heating rate of 5℃ / min under N2 atmosphere and calcined for 4h. After cooling, it was ground through a 200-mesh sieve to obtain the target composite material Cat-11.

[0081] Example 12 A method for preparing a low-leaching nickel-based aluminum-doped spinel / functionalized biochar composite disinfectant material includes the following steps: Carrier surface functionalization: 5.0g of rice husk powder (100 mesh) was immersed in 100mL of modifier aqueous solution for 4h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%. The mixture was dried at 80℃ for 12h.

[0082] Precursor complexation assembly: Dissolve 2.91 g Ni(NO3)2·6H2O, 7.68 g Fe(NO3)2·9H2O, and 0.38 g Al(NO3)3·9H2O in 100 mL of deionized water, add the above precursor, and stir for 30 min.

[0083] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 h to induce coprecipitation; then it was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 12 h, followed by natural cooling.

[0084] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12 h; then heated to 550℃ at a heating rate of 5℃ / min under N2 atmosphere and calcined for 4 h. After cooling, it was ground through a 200-mesh sieve to obtain the target composite material Cat-12.

[0085] Example 13 A method for preparing a low-leaching zinc-magnesium composite spinel / functionalized biochar composite disinfectant material includes the following steps: Carrier surface functionalization: 5.0 g of wheat straw powder (100 mesh) was impregnated in 100 mL of modifier aqueous solution for 4 h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%. The mixture was dried at 80℃ for 12 h.

[0086] Precursor complexation assembly: Dissolve 1.49 g Zn(NO3)2·6H2O, 1.28 g Mg(NO3)2·6H2O, 7.68 g Fe(NO3)2·9H2O, 0.22 g Ce(NO3)3·6H2O, and 0.22 g La(NO3)3·6H2O in 100 mL of deionized water, add the above precursors, and stir for 30 min.

[0087] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 h to induce coprecipitation; then it was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 12 h, followed by natural cooling.

[0088] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12 h; then heated to 550℃ at a heating rate of 5℃ / min under N2 atmosphere and calcined for 4 h. After cooling, it was ground through a 200-mesh sieve to obtain the target composite material Cat-13.

[0089] Example 14 A method for preparing a low-leaching zinc-nickel composite spinel / functionalized biochar composite disinfectant material includes the following steps: Carrier surface functionalization: 5.0 g of wheat straw powder (100 mesh) was impregnated in 100 mL of modifier aqueous solution for 4 h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%. The mixture was dried at 80℃ for 12 h.

[0090] Precursor complexation assembly: Dissolve 1.49 g Zn(NO3)2·6H2O, 1.45 g Ni(NO3)2·6H2O, 6.46 g Fe(NO3)2·9H2O, and 0.87 g Ce(NO3)3·6H2O in 100 mL of deionized water, add the above precursors, and stir for 30 min.

[0091] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 h to induce coprecipitation; then it was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 12 h, followed by natural cooling.

[0092] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12 h; then heated to 550℃ at a heating rate of 6℃ / min under N2 atmosphere and calcined for 4 h. After cooling, it was ground through a 200-mesh sieve to obtain the target composite material Cat-14.

[0093] Example 15 A method for preparing a low-dissolution spinel / functionalized biochar composite disinfectant material includes the following steps: Carrier surface functionalization: 4.0 g of wheat straw powder (100 mesh) was impregnated in 100 mL of modifier aqueous solution for 4 h. The modifier was a mixture of urea and thiourea at a mass ratio of 1:1, with a total mass fraction of 10%. The mixture was dried at 80℃ for 12 h.

[0094] Precursor complexation assembly: Dissolve 2.97 g Zn(NO3)2·6H2O, 7.68 g Fe(NO3)2·9H2O, and 0.43 g Ce(NO3)3·6H2O in 150 mL of deionized water (the mass concentration of the metal salt is approximately 7.4%, which is close to but slightly lower than the lower limit of 8% in claim 8), add 4.0 g of the above precursor (the ratio of solution to precursor is 37.5 mL:1 g, which exceeds the upper limit of 25 mL:1 g in claim 8), and stir for 30 min.

[0095] In-situ coprecipitation and hydrothermal crystallization: Ammonia was added dropwise to adjust the pH of the system to 10.0, and the mixture was stirred at room temperature for 2 h to induce coprecipitation; then it was transferred to a hydrothermal reactor and hydrothermally reacted at 180℃ for 12 h, followed by natural cooling.

[0096] High-temperature pyrolysis lattice reconstruction: The reaction product was washed with deionized water until neutral and dried at 80℃ for 12 h; then heated to 550℃ at a heating rate of 5℃ / min under N2 atmosphere and calcined for 4 h. After cooling, it was ground through a 200-mesh sieve to obtain the target composite material Cat-15.

[0097] In summary, this invention provides a low-dissolution spinel / functionalized biochar composite disinfectant material, its preparation method, and its application. This material combines high disinfection efficiency with controllable metal leaching. Taking Example 1 (Cat-1) as an example, within the pH range of 3-9, its inactivation rate against Escherichia coli and Staphylococcus aureus remains at 99.6% or higher. Under the conditions of pH 3.0, a dosage of 0.1 g / L, 5.0 mM H2O2, and a reaction time of 30 min, the leaching rates of Zn and Fe ions are 1.6% and 0.9%, respectively, and within the pH range of 3–9, the leaching rates of Zn and Fe are lower than 1.6% and 0.9%, respectively. The structure exhibits strong stability. Characterization and comparative testing results indicate that the MN and MS chemical bonds between the nitrogen-sulfur co-doped biochar support and the spinel active component, as well as Ce lattice doping, are key to maintaining structural stability. Specifically, when the support is absent (Ref-1), the Zn and Fe dissolution rates increase to 7.5% and 4.6% respectively under acidic conditions at pH=3. When only pure spinel remains without the support (Ref-2), the Zn and Fe dissolution rates reach as high as 8.3% and 6.5% respectively. In contrast, the Zn and Fe dissolution rates of the control without Ce doping (Cat-3) under acidic conditions are 2.8% and 1.8% respectively. The optimal embodiment (Cat-1) consistently maintains Zn and Fe dissolution rates below 1.6% and 0.9%, verifying the necessity of the proposed structural design. The process is highly tolerant, and the raw material cost is low. The verification results show that the obtained materials can maintain the above-mentioned low dissolution and high bactericidal properties within the range of hydrothermal temperature of 160-200℃ and calcination temperature of 450-600℃. The materials are made from agricultural waste such as wheat straw and rice husks, and have a wide range of sources.

[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention in any way. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can be modified and replaced in several simple ways, and these modifications and replacements are all within the scope of protection covered by the claims.

Claims

1. A low-leaching spinel / functionalized biochar composite disinfection material, characterized in that, It includes a functionalized biochar carrier, which is rich in nitrogen and sulfur heteroatom functional groups and has spinel active components coordinated and bonded to it via MN and MS. The chemical formula of the spinel active component is: M a Fe b R c O4, where M is one or more of Zn, Mg, and Ni; R is one or more of Ce, La, and Al; a, b, and c are molar coefficients that satisfy charge balance and lattice structure, where 0 <c≤0.2。 2. The low-leaching spinel / functionalized biochar composite disinfection material according to claim 1, characterized in that, The functionalized biochar carrier is prepared by pyrolysis of agricultural waste modified with nitrogen and sulfur sources.

3. The low-leaching spinel / functionalized biochar composite disinfection material according to claim 2, characterized in that, The functionalized biochar carrier was prepared by pyrolysis of a compound of urea and thiourea.

4. The low-leaching spinel / functionalized biochar composite disinfection material according to claim 3, characterized in that, The mass ratio of urea to thiourea is (0.8-1.2):

1.

5. The low-leaching spinel / functionalized biochar composite disinfection material according to claim 1, characterized in that, In the chemical formula of the spinel-type ferrite, M is Zn, R is Ce, and the chemical formula is ZnFe. b Ce c O4, where b = 2 - c, 0 < c ≤ 0.

2.

6. A method for preparing a low-leaching spinel / functionalized biochar composite disinfection material as described in any one of claims 1-5, characterized in that, include: The biomass raw material is impregnated in an aqueous solution containing nitrogen and / or sulfur compounds and then dried to obtain a functionalized precursor. A metal salt solution containing M, Fe, and R was mixed with a functionalized precursor, the pH value was adjusted, and co-precipitation, hydrothermal reaction, and calcination under an inert atmosphere were carried out sequentially to obtain a low-dissolution spinel / functionalized biochar composite disinfection material.

7. The preparation method of the low-leaching spinel / functionalized biochar composite disinfection material according to claim 6, characterized in that, The biomass raw material is wheat straw powder or rice husk powder; the mass concentration of the aqueous solution containing nitrogen and / or sulfur compounds is 5%-15%; the mass ratio of nitrogen source to sulfur source in the aqueous solution containing nitrogen and / or sulfur compounds is (0.8-1.2):1; the soaking time is 3-5 hours; the drying temperature is 70-90℃ and the drying time is 8-16 hours.

8. The preparation method of the low-leaching spinel / functionalized biochar composite disinfection material according to claim 6, characterized in that, In the metal salt solution containing M, Fe, and R, the mass concentration of the metal salts M, Fe, and R is 8%-15%, and the molar ratio of M, Fe, and R in the metal salt solution satisfies the general chemical formula for spinel-type ferrites M a Fe b R c The molar ratio of the corresponding elements in O4, the ratio of the metal salt solution containing M, Fe, and R to the functionalized precursor is (15-25) mL:1g; the pH value is adjusted by titration with ammonia water, and the pH value adjustment range is 9-11; the hydrothermal reaction temperature is 160-200℃, and the time is 10-14h; the calcination temperature is 450-600℃, and the time is 3-5h; the inert atmosphere is nitrogen atmosphere; before calcination, the hydrothermal reaction product is washed to neutral and dried at 70-90℃ for 8-16h.

9. The application of the low-leaching spinel / functionalized biochar composite disinfection material according to any one of claims 1-5 in water treatment disinfection.

10. The application of the low-leaching spinel / functionalized biochar composite disinfection material according to claim 9 in water treatment disinfection, characterized in that, include: Low-leaching spinel / functionalized biochar composite disinfectant material and H2O2 are added to the water to be treated, and the reaction is stirred to inactivate pathogenic microorganisms. The dosage of low-leaching spinel / functionalized biochar composite disinfectant material is 0.05-0.2 g / L, the concentration of H2O2 is 2-8 mM, the reaction time is 20-40 min, and the pH value of the water to be treated is 3-9.